Cinders : a chicken Cinderella - Brett, Jan, 1949- (New York, NY : G.P. Putnam's Sons, an imprint of Penguin Group (USA) Inc., 2013)
Cinders, the most picked upon hen in the flock, becomes the most loved by Prince Cockerel when she arrives at his ball looking so beautiful that even her bossy sisters do not recognize her.
Pub Weekly, October 2013
3.6
K-3
Keywords: Chickens -- Folklore; Folklore; Fairy tales; Chickens -- Folklore; Folklore; Fairy tales; Chickens -- Folklore; Folklore; Fairy tales; Folklore; Fairy tales; Picture books for children